A study of the relationship between American Sign Language and English literacy - and Strong, Michael; Prinz, Philip M. (The Journal of Deaf Studies and Deaf Education, 1997)
This article presents the findings of a study of the relationship between American Sign Language (ASL) skills and English literacy among 160 deaf children. Using a specially designed test of ASL to determine three levels of ASL ability, we found that deaf children who attained the higher two levels significantly outperformed children in the lowest ASL ability level in English literacy, regardless of age and IQ. Furthermore, although deaf children with deaf mothers outperformed deaf children of hearing mothers in both ASL and English literacy, when ASL level was held constant, there was no difference between these two groups, except in the lowest level of ASL ability. The implication of this research is straightforward and powerful: Deaf children's learning of English appears to benefit from the acquisition of even a moderate fluency in ASL.